The railroad, the telegraph, and other technologies - Uhl, Xina M. (Westward expansion: America's push to the Pacific., 2018)
Introduces some of the inventions and technologies that changed the American landscape in the nineteenth century including the telegraph, the steel plow, and the railroad. Includes a glossary and resources for further research.